Leukotriene receptor antagonist reduces inflammation and alveolar bone loss in a rat model of experimental periodontitis - Moro, Marcella G. (2021)
Background: Leukotrienes (LTs) participate in the process of tissue damage in periodontal disease by leukocyte chemotaxis and osteoclastic activation. The activation of Cysteinyl-LT receptor is associated with increased expression of proinflammatory molecules and osteoclastogenesis. However, its implications on periodontal disease progression have not been studied. The present study evaluated the effect of the cysteinyl-LT receptor antagonist (montelukast [MT]) on ligature-induced experimental periodontitis (EP) in rats. Methods: Adult male Wistar rats were subjected to bilateral ligature-induced periodontitis and orally treated with MT (at doses of 10 or 30 mg/kg/d, MT10, and MT30, respectively). Sham animals had the ligatures immediately removed and received placebo treatment. Sets of animals were euthanized 7, 14, or 21 days after ligature placement and the mandibles were removed for macroscopic evaluation of alveolar bone loss (ABL). In addition, histological analysis of periodontal tissues, myeloperoxidase (MPO) activity of gingival tissues, and periodontal tissue expression of collagen type I, RUNX2, RANK, RANKL, OPG, BLT1, Cys-LTR1, LTA4H, and LTC4S were also analyzed. Results: MT significantly reduced ABL at 14 (MT10 and MT30) and 21 days (MT10) (P < 0.05), gingival MPO at 7 (MT10) and 14 days (MT30) (P < 0.05), LTA4H, BLT1 and LTC4S gene expression on day 14 day (MT30, P < 0.05) and increased RUNX2 expression on day 14 (MT30, P < 0.05). Conclusion: Systemic therapy with MT decreases periodontal inflammation and ABL in ligature-induced periodontitis in rats.